2021
DOI: 10.1007/s40891-021-00276-9
|View full text |Cite|
|
Sign up to set email alerts
|

Microbial-Induced Desaturation in Stratified Soil Conditions

Abstract: A feasibility study was performed to assess the potential of microbially induced desaturation and precipitation (MIDP) through denitrification to reduce the risk of earthquake-induced liquefaction and improve the resilience of embankments along the lower Fraser River in Richmond, British Columbia, Canada. The denitrification process produces nitrogen gas, which gradually desaturates the soil, and dissolved inorganic carbon, which in presence of dissolved calcium results in precipitation of calcium carbonate mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The percolation threshold saturation was not defined by Wang, Van Paassen, Gao, et al. (2020), but other tests (Pham, Van Paassen, & Van der Star, 2018; Stallings Young et al., 2021) reported the water saturation at which gas started to migrate and no further desaturation was obtained, ranging between 50% and 80%.…”
Section: Results and Analysismentioning
confidence: 98%
See 3 more Smart Citations
“…The percolation threshold saturation was not defined by Wang, Van Paassen, Gao, et al. (2020), but other tests (Pham, Van Paassen, & Van der Star, 2018; Stallings Young et al., 2021) reported the water saturation at which gas started to migrate and no further desaturation was obtained, ranging between 50% and 80%.…”
Section: Results and Analysismentioning
confidence: 98%
“…In natural sediments it may be difficult to get a precise value for S v , due to the heterogeneity of the pore structure. For example, in a sandy-silt stratified soil system this threshold may be higher as silt lenses can prevent upward migration of gas and cause the gas phase to spread laterally (Stallings Young et al, 2021). Thus, the change in liquid fraction is described using:…”
Section: Saturation-permeability Relationshipmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, He et al [27] confirmed that nitrogen bubbles that were produced by bacteria can effectively reduce the saturation and improve the liquefaction resistance of soil through triaxial testing. Larger scale experiments, including field trials on microbial-induced desaturation, have been performed [29,30]. Li [31] pointed out that nitrogen bubbles lacked stability under the conditions of groundwater seepage and, therefore, proposed a new method to deal with the liquefaction resistance of liquefiable soil.…”
Section: Introductionmentioning
confidence: 99%